1982
DOI: 10.1007/bf00016408
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a strobe light eel exclusion scheme

Abstract: In the laboratory and field, American eels (Anguilla rostrata) showed a strong avoidance of white strobe light . Eels avoided low light intensities for all strobe flash frequencies tested, and showed no behavioural adaptation to the light source over a prolonged time period . A strobe light barrier was 65-92% effective in repelling upstream migrating eels at Saunders GS on the St . Lawrence River. All size classes of eels were repelled, but effectiveness appeared to be reduced for smaller eels . IntroductionMa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…Chinook salmon exhibited an attraction to dim mercury light but coho salmon did not. These results were not unlike most fish guidance studies, which showed repulsion by strobe light (Fields and Finger 1956;Patrick 1982Patrick , 1983Patrick et al 1982Patrick et al , 1985Sager el al. 1987) and attraction to dim mercury lights (Wickham 1973).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chinook salmon exhibited an attraction to dim mercury light but coho salmon did not. These results were not unlike most fish guidance studies, which showed repulsion by strobe light (Fields and Finger 1956;Patrick 1982Patrick , 1983Patrick et al 1982Patrick et al , 1985Sager el al. 1987) and attraction to dim mercury lights (Wickham 1973).…”
Section: Discussionmentioning
confidence: 99%
“…Although the patterns are complex, several trends have emerged. Generally fish are repelled by strobe lights (Patrick 1982(Patrick , 1983Patrick et al 1982Patrick et al , 1985Sageret al 1987), whereas fish may exhibit a mixture of attraction and repulsion behavior to steady lighting (Wickham 1973;Taft et al 1988).…”
mentioning
confidence: 99%
“…As silver eels follow the main flow (Jansen et al., ), the orientation of the water intake with respect to the main channel influences the probability of turbine passage (Bau et al., ). Different types of barriers have been proposed to divert eels from turbine passage, such as fish‐friendly trashracks (Raynal, Chatellier, Courret, Larinier, & David, ; Raynal, Courret, Chatellier, Larinier, & David, ), flow field manipulation (Piper et al., ), light (Hadderingh, Van Der Stoep, & Hagraken, ; Patrick, Sheehan, & Sim, ) and infrasound barriers (Sand, Enger, Karlsen, Knudsen, & Kvernstuen, ; Sand et al., ). The installation of bypasses is also a mitigation measure to prevent passages through turbines (Durif et al., ; Gosset et al., ; Haro, Watten, & Noreika, ). Environmental conditions: In a period of low discharge, when the flow through the turbine is high compared to the flow over weir, more eels will pass through the turbines than at high discharge, when the turbine flow is small compared to the weir flow. Obstacle location within the catchment: As eels are not uniformly distributed within a river catchment (Ibbotson, Smith, Scarlett, & Aprhamian, ), the number of eels impacted by a given facility depends on the number of eels that settle upstream the facility.…”
Section: Component 3—fragmentation and Habitat Loss: Fragmentation Bymentioning
confidence: 99%
“…Pulsed lighting has regularly been found to act as a repellent to organisms, with limited evidence for adaptive responses (e.g. Hamel, Brown, & Chipps, 2008;Linhart, 1984;Nemeth & Anderson, 1992;Patrick, Sheehan, & Sim, 1982;Sullivan et al, 2016), and to be less of an attractant than continuous lighting (Gehring, Kerlinger, & Manville, 2009). Areas experiencing pulsed lighting may thus as a consequence be avoided and may contribute to the fragmentation of habitats.…”
Section: Developmentsmentioning
confidence: 99%